Discomfort towards peers causes therapy-related stress in children and adolescents on daily rhGH therapy - Corica, Domenico; Lugarà, Cecilia; Ferraloro, Chiara; Alibrandi, Angela; La Malfa, Valentina; Pecoraro, Maria; Pepe, Giorgia; Morabito, Letteria Anna; Aversa, Tommaso; Wasniewska, Malgorzata Gabriela (Frontiers in Endocrinology, 2025)
IntroductionRecombinant human growth hormone (rhGH) therapy is a long-term, daily, injective treatment, which can be burdened by poor adherence affected by several factors. In addition, chronic daily administration of rhGH may cause stress and discomfort in the child and the caregivers, independent of the degree of adherence. Aims of this study are: 1. to evaluate the degree of adherence and the presence of stress related to daily treatment with rhGH on the basis of data reported by patients and caregivers; 2. to assess which factors influence adherence to rhGH therapy and therapy-related stress.MethodsPatients on rhGH therapy for at least one year, diagnosed with isolated GH deficiency (GHD) or on rhGH therapy because small for gestational age (SGA) were included. Patients and/or caregivers were administered a questionnaire on family background, duration and management of rhGH therapy, perception of effectiveness, adherence, fear of needles, chronic therapy-related stress, discomfort towards peers related to chronic treatment.ResultsSeventy patients were recruited (mean age 11.7 ± 2.86 years). Good adherence was reported in 82.9% of cases while medium/poor adherence was reported in 17% of the cases. Fear of needles was reported in 25.7% of cases and discomfort towards peers related to chronic treatment in 22.9% of cases. Therapy-related stress was declared in 41.4% of cases. At the univariate regression analysis, therapy-related stress was influenced by fear of needles (OR 2.9, 95%CI 1.05-8.97; p=0.044) and discomfort towards peers (OR 4.4, 95%CI 1.32-14.59; p=0.015). Multivariate regression analysis confirmed the significant influence of discomfort towards peers on chronic therapy-related stress (OR 4.84, 95%CI 1.30-17.99; p=0.019) independently of gender, age, pubertal stage and fear of needles.ConclusionDiscomfort towards peers related to chronic treatment was associated to therapy-related stress in childhood, despite a high degree of adherence. These factors should be identified early to plan strategies to mitigate their negative impact on the quality of life of patients treated with rhGH.